The effect of preferred background music on mathematical performance of adolescents with mathematics difficulties - Milman, Alex; Paz-Baruch, Nurit (Frontiers in Education, 2025)
IntroductionThere is substantial evidence indicating the favorable influence of music on task performance; however, few studies have explored the specific impact of background music on mathematics achievements. This paper addresses the gaps in the existing literature and explores the effect of background music on adolescents' performance in mathematics. It also examines the impact of preferred background music on students' mathematical achievements.MethodsData were collected from 65 10th-grade students with difficulties in mathematics, who were randomly assigned to two study groups. All participants took three mathematics tests in algebra. The experimental group solved the tests under three different conditions: without background music, with background music, and with self-selected background music. The control group took the tests without background music.ResultsThe results indicated that solving mathematics tasks while listening to self-selected background music enhances students' mathematical performance compared to solving mathematics tasks with predetermined background music or without any background music.DiscussionThese findings add to the theoretical literature regarding the impact of background music on students' mathematics achievements and provide practical guidance for mathematics educators in their discourse on students' mathematics learning in class. The findings underscore the necessity for further investigations to elucidate the underlying factors of the effects of background music on learning.